2021
DOI: 10.12996/gmj.2021.42
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Malathion Exposure on Renal Oxidant and Antioxidant Balance in Rats

Abstract: Objective: Pesticides have been used in agriculture to enhance food production by eradicating undesired insects and controlling disease vectors. Malathion is one of the most widely used organophosphate pesticides. However, it has been postulated that organophosphate pesticides lead to oxidative stress through formation of excessive reactive oxygen species and disrupting the antioxidant defense systems. Methods: Four groups (n=6) were designed to evaluate the effects of different doses of acute malathion exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The liver and kidney are among the primary affected organs of malathion toxicity, which is mediated by oxidative stress initiated by ROS [5], and higher levels of ROS result in tissue damage [1]. Pasaoglu and his colleagues reported that organophosphorus pesticides caused an increased production of reactive oxygen species (ROS) that induce oxidative stress, moreover, it attenuates the antioxidant defense capacity [6]. Yonar et al (2017) reported that curcumin restored the activities of key antioxidants, including superoxide dismutase, catalase, glutathione peroxidase, and glutathione-S-transferase [7].…”
Section: Introductionmentioning
confidence: 99%
“…The liver and kidney are among the primary affected organs of malathion toxicity, which is mediated by oxidative stress initiated by ROS [5], and higher levels of ROS result in tissue damage [1]. Pasaoglu and his colleagues reported that organophosphorus pesticides caused an increased production of reactive oxygen species (ROS) that induce oxidative stress, moreover, it attenuates the antioxidant defense capacity [6]. Yonar et al (2017) reported that curcumin restored the activities of key antioxidants, including superoxide dismutase, catalase, glutathione peroxidase, and glutathione-S-transferase [7].…”
Section: Introductionmentioning
confidence: 99%